Kowtowing to a Non-natural Realm - Bedke, Matthew S. (Journal of moral philosophy, 2022)
Abstract Non-naturalists face a dilemma. They either leave their normative views hostage to a non-natural realm, which is immoral, or they do not, which is irrational. David Enoch has argued that the problem rests on cases of junk knowledge — conditionals that cannot be used to expand knowledge via modus ponens. Camil Golub has suggested that the dilemma rests on questionable assumptions about how we might come to know about the non-natural. Here I reply to these worries, sharpen the dilemma, and situate it in the literature on doxastic wrongs.